Symptoms of Borderline Personality Disorder Predict Interpersonal (but not Independent) Stressful Life Events in a Community Sample of Older Adults - Powers, Abigail D. (2013)
Individuals with borderline personality disorder (BPD) often experience stressful life events at a higher frequency than those without BPD. It is less clear what specific types of events are involved in this effect, and it has not been determined whether some features of BPD are more important than others in accounting for this effect. The latter issue is important in light of the heterogeneous nature of this diagnostic construct. These issues were examined in a large, representative community sample of men and women, ages 55–64. Ten Diagnostic and Statistical Manual of Mental Disorders (4th ed., text rev., DSM–IV–TR, Washington, DC, American Psychiatric Association, 2000) personality disorders were assessed at baseline using the Structured Interview for DSM-IV Personality: SIDP-IV (B. Pfohl, N. Blum, & M. Zimmerman, 1997, Washington, DC, American Psychiatric Press). Life events were measured at three sequential assessments following baseline at 6-month (N = 1,294), 12-month (N = 1,070), and 18-month (N = 837) follow-ups. Stressful life events were identified using a self-report questionnaire (LTE-Q; List of Threatening Experiences Questionnaire: A subset of prescribed life events with considerable long-term contextual threat by T. Brugha, C. Bebbington, P. Tennant, and J. Hurry, 1985, Psychological Medicine, Vol. 15, pp. 189–194.) followed by a telephone interview. Only borderline personality pathology was related to an increase in the frequency of interpersonal stressful life events. Three specific symptoms of BPD were largely responsible for this connection: unstable interpersonal relationships, impulsivity, and chronic feelings of emptiness (negative association). Symptoms of avoidant and schizoid personality disorders were associated with a reduced number of stressful life events that are considered to be outside a person’s control (e.g., serious illness, injury, or death of a loved one). None of the personality disorders predicted an increase in the number of stressful financial events (e.g., major financial crisis). These findings suggest that, as individuals approach later life, certain features of BPD continue to serve as important risk factors for stressful life events of an interpersonal nature.